Mesoscopic structure evidenced by AC dielectric nonlinearities in Sr(0.75)Ba(0.25)Nb(2)O(6) relaxor ferroelectric thin films - Santos, I. A.; Guerra, J. de Los S. [UNESP]; Araujo, E. B. [UNESP]; Mendes, R. G.; Eiras, J. A. (Iop Publishing Ltd, 2008)
The AC electric field and temperature dependences of the dielectric permittivity for strontium barium niobate (Sr(0.75)Ba(0.25)Nb(2)O(6)) relaxor ferroelectric thin films have been investigated. The results indicate the existence of a true mesoscopic structure evidenced by the nonlinear dielectric response of these films, which is similar to those observed for bulk relaxor ferroelectrics. A tendency for a temperature dependent crossover from a linear to a quadratic behaviour of the dielectric nonlinearity was observed, indicating an evolution from paraelectric to glass-like behaviour on cooling the samples towards the freezing temperature transition.